2012
DOI: 10.1002/ejoc.201200383
|View full text |Cite
|
Sign up to set email alerts
|

Recent Highlights in Ketenimine Chemistry

Abstract: Selected recent developments in the chemistry of ketenimines are presented, demonstrating that heterocumulenes of this class are versatile reactive intermediates in the synthesis of nitrogenated heterocycles. This microreview includes examples of intramolecular nucleophilic and radical additions, biradical cyclizations, 4π‐ and 6π‐electrocyclic ring closures, [2+2], [3+2] and [4+2] cycloadditions, ketenimine‐to‐nitrile rearrangements and 1,3‐X, 1,5‐X and 1,5‐H shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 96 publications
0
43
0
Order By: Relevance
“…In contrast, under the same reaction conditions, N-phenyl and/or N-carboxyl ynamides react with indole through the more classical addition to the a-position, albeit with the concomitant loss of the EWG. This process not only grants access to indolylamidines but also suggests a mild in situ generation of ketenimines, [27] which could be of considerable synthetic interest. Studies in these directions are currently underway in our laboratory and will be reported in due course.…”
mentioning
confidence: 99%
“…In contrast, under the same reaction conditions, N-phenyl and/or N-carboxyl ynamides react with indole through the more classical addition to the a-position, albeit with the concomitant loss of the EWG. This process not only grants access to indolylamidines but also suggests a mild in situ generation of ketenimines, [27] which could be of considerable synthetic interest. Studies in these directions are currently underway in our laboratory and will be reported in due course.…”
mentioning
confidence: 99%
“…Keteneimines constitute an important class of highly reactive species, isoelectronic with ketene and allene. These molecules can undergo a large panel of reactions and several recent reviews were devoted to these useful synthetic intermediates (Alajarin et al, 2012;Lu & Wang, 2012). The parent species CH 2 5 5C5 5NH, which was first synthetized in solution almost one century ago (Staudinger & Meyer, 1919) and more recently in the gas-phase by pyrolysis of azidopropionitrile, N 3 CH 2 CH 2 CN (Pinto et al, 2012), is also of astrophysical relevance (Danger et al, 2013).…”
Section: Keteneimines Ch 2 5 5c5 5nhmentioning
confidence: 99%
“…As isocyanides have been explored as the surrogate of CO because of the similarity of their reactivity, [13,14] we further conceived that as the analogue of difluorocarbene,t he difluoroketenimine might be obtained through the reaction of difluorocarbene and isocyanide.K etenimines are in general less reactive compared to their ketene counterparts and ketenimine-imine [2+ +2] cycloadditions are rare. [15,16] To our knowledge,d ifluoroketenimines are not documented in the literature.Itcan be expected that the introduction of fluorine substituents on the C-terminus activates the ketenimines,thus possibly leading to facile [2+ +2] cycloaddition to give a,adifluoro-b-lactams or a,a-difluoro-b-amino-acid derivatives after hydrolysis (Scheme 1c). Herein, we report the [2+ +2] cycloaddition of imines and difluoroketenimines generated in situ via the reaction of difluorocarbene and isocyanides.…”
mentioning
confidence: 93%